Diagnóstico do saneamento básico no município de Jaboticaba/RS por meio do indicador de salubridade ambiental - Scolari, Tainan Weber (2022)
The Environmental Health Indicator (ISA) was proposed by the São Paulo State Sanitation Council (CONESAN) to assess the environmental situation of São Paulo municipalities, with the main premise of presenting a numerical value that represents the level of environmental health. The ISA evaluates several sanitation components and its value varies from 0 to 1 (or 0% to 100%), and the closer to 1, the greater the environmental healthiness of the analyzed region. Despite having been created to evaluate the municipalities of São Paulo, the ISA started to be used in several regions of Brazil, and its formulation varied according to the characteristics of the evaluated locations. The general objective of this study was to carry out a diagnosis of the environmental sanitation systems in the municipality of Jaboticaba/RS, through the ISA, ascertaining the current conditions for the development of a prognosis aimed at improvements. To this end, a survey of municipal data was carried out, which were compiled and organized so that the values of the 3rd and 2nd order indicators could be obtained, resulting in the value of the ISA for each municipal micro-region, so that, later on, if you could get the general value of the, here called, ISA/JAB. The value of the ISA/JAB was obtained for the micro-regions of the municipality, both rural and urban, carrying out an in-depth analysis of all components of municipal sanitation. The general value of the ISA/JAB was 51.82%, which fits the region as having medium health. The study pointed out the need for improvement in some spheres of sanitation, especially sanitary sewage, which need improvements to increase local environmental health. The best results were presented by the Vector Control Indicator, with 90.44%, followed by the Water Supply Indicator, with 81.70%.